ANALISIS PENERIMAAN PENGGUNA APLIKASI SUPER CONSIGN DENGANTECHNOLOGY ACCEPTANCE MODEL - Sudirman; Harwandi, Yeviyen; Sahareani, Yeni (STMIK KHARISMA Makassar, 2023)
Super Consign is an application for selling used and new goods in the form of laptops and gaming accessories. Super Consign is a new application, so no research has been conducted to measure the level of acceptance of this application. Acceptance of the Super Consign application is one of the factors that support the continued use of the application. In this study, the measurement of the Super Consign application was carried out using the Technology Acceptance Model method which consists of 3 variables, namely Actual Use, Perceived Ease of Use, and Perceived Usefulness. This study used 31 respondents and tested validity and reliability using the SPSS application. The results of this study, have a percentage of 70.64% on the use of the application Actual Use, on the perceived ease of use variable is 72.09%, and on the percentage value of the perceived usefulness variable is 69.19%. So that the Super Consign application can be accepted.